Psychological factors predictors of students' academic achievement in Yoruba language in senior secondary schools in Egbeda local government, Oyo state, Nigeria (2016)
This paper examined the relationship among selected psychological factors (locus of control, self-concept and motivation) and students’ academic achievement in Yoruba language in Egbeda local government area, Oyo state. The study also examined which of the selected psychological factors will most predict academic achievement in Yoruba language. Four hundred and eighty class two students randomly selected from nine senior secondary schools out of twenty six in Egbeda local government area participated in the study in which four research questions were answered. Four research instruments were used in this study: students’ locus of control scale (SLOCS)(r=.76); students’ self-concept scale (SSCS)(r=.82); students’ motivation scale (SMOTS)(r=.84); and Yoruba language achievement test (ylat)(86). Data collected were analyzed using descriptive statistics of mean and standard deviation: inferential statistics of Pearson products moment correlation and multiple regression findings revealed that there is no significant correlation between students’ academic achievement in Yoruba language and locus of control (r=.060,p>.05). The correlation between student academic achievement in Yoruba language and motivation is not significant (r=-.067.p> .05). However, there is no significant positive correlation between students’ self-concept and academic achievement in Yoruba language (r=.067, p <.05) the three Pshycological factor can predict students’ academic achievement in Yoruba language ( β0.15; t=2.06; p<0.05)>; sloc ( β=.079; t=1.642, p>.05)>; ssc ( β=.040;t=-.736; p>.05) with motivation being the most, followed by locus of control and self-concept.